Evaluation of brain and spinal cord lesion distribution criteria at disease onset in distinguishing NMOSD from MS and MOG antibody-associated disorder. (May 2021) - Cai, Meng-Ting; Zheng, Yang; Shen, Chun-Hong; Yang, Fan; Fang, Wei; Zhang, Yin-Xi; Ding, Mei-Ping
Objective: To validate the recently proposed imaging criteria in distinguishing aquaporin-4 antibody (AQP4-ab)-seropositive neuromyelitis optica spectrum disorder (NMOSD) from multiple sclerosis (MS) and myelin oligodendrocyte glycoprotein antibody-associated disorder (MOG-AD) at disease onset in a Chinese population. Methods: We enrolled 241 patients in this retrospective study, including 143 AQP4-ab-seropositive NMOSD, 73 MS, and 25 MOG-AD. Cacciaguerra's criteria were described as fulfillment of at least 2/5 conditions including the absence of the combined juxtacortical/cortical lesions, the presence of longitudinal extensive transverse myelitis (LETM) lesions, the presence of periependymal-lateral ventricles lesions, the absence of Dawson's fingers lesions, and the absence of periventricular lesions. Results: Fulfillment of at least 3/5 conditions was able to differentiate NMOSD from MS with a good diagnostic performance (accuracy = 0.92, sensitivity = 0.91, specificity = 0.93), yet failed to differentiate NMOSD from MOG-AD. LETM lesions showed the highest accuracy (0.78), sensitivity (0.70), and specificity (0.97) for NMSOD. Conclusion: Our research suggested the utility of Cacciaguerra's criteria in a Chinese population at disease onset. A better diagnostic performance in NMOSD could be attained with at least 3/5 conditions fulfilled. Yet their utility in distinguishing NMOSD from MOG-AD was limited.